PENDUGAAN BOBOT BADAN MELALUI UKURAN TUBUH PADA KAMBING KEJOBONG BETINA DEWASA DI KELOMPOK TANI TERNAK NGUDI DADI KABUPATEN PURBALINGGA - Annisah Nur Rahmah; Setya Agus Santosa; Dewi Puspita Candrasari (ANGON: Journal of Animal Science and Technology, 2022)
Background. This study aims to compare the body size and body weight of adult female Kejobong goats in the Ngudi Dadi Livestock Farmer Group with the Keputusan Menteri Pertanian Republik Indonesia Nomor 301/Kpts/SR.120/5/2017 tentang Penetapan Rumpun Kambing Kejobong and obtaining a body weight guessing formula based on the body measurements of an adult female Kejobong goat. The research was conducted on February 1 - March 1, 2022, located in the Ngudi Dadi Livestock Farmer Group which is the center area for the development of Kejobong goats in Kejobong District, Purbalingga Regency. Materials and Methods. The research material used was 97 female Kejobong goats aged >12 months. The research method used is a survey with data retrieval techniques using purposive sampling. The data obtained is analyzed using descriptive analysis, linear regression analysis, correlation analysis, determination, accuracy test and t test. Results. The results showed that the adult female Kejobong goat had an average body length of 52.05 ± 7.11 cm, a chest circumference of 73.43 ± 6 cm, a shoulder height of 68.32 ± 4.86 cm and a body weight of 31.31 ± 7.45 kg. The correlation coefficient is 0.909 and the coefficient of determination is 82.6%. The regression equation obtained is Y = -57,378 + 0.238(X1) + 0.746(X2) + 0.314(X3) with Y: body weight, X1: body length, X2: chest circumference, X3: shoulder height. Body length contributed 19%, chest circumference 64% and shoulder height 17% in the regression equation. The accuracy test showed that the obtained formula had an average accuracy of 92.46%. Based on research, it can be concluded that the body size and body weight of adult female Kejobong goats in the Ngudi Dadi Livestock Farmer Group is lower than the standard body size and body weight of adult female Kejobong goats that have been established by the Keputusan Menteri Pertanian Republik Indonesia Nomor 301/Kpts/SR.120/5/2017 tentang Penetapan Rumpun Kambing Kejobong. Conclusion. For the benefit of time efficiency, the presumption of body weight is only recommended using chest circumference only because it has the largest relative contribution (64%).